Mechanisms of isorhamnetin inhibition of osteoclast differentiation: insights from molecular dynamics simulations and in vitro/in vivo experiments - Zhou, Yi; Li, Shaoshuo; Hong, Bowen; Wang, Zihan; Shao, Yang; Wu, Mao; Wang, Jianwei (Frontiers in Pharmacology, 2025)
BackgroundOsteoporosis (OP) represents a widespread bone remodeling disorder within the domain of orthopedics, markedly compromising the quality of life in the elderly population. The need to develop more efficient therapeutic approaches to attenuate bone resorption by suppressing the excessive activation of osteoclasts (OCs) remains urgent. The plant flavonoid Isorhamnetin (Iso), recognized for its potent antioxidant properties, has been the subject of extensive research regarding its potential in treating bone-related conditions.MethodThis study adopts a comprehensive methodology to evaluate Iso’s impact on bone metabolism and its therapeutic possibilities for treating OP. By integrating network pharmacology, molecular dynamics simulations, and surface plasmon resonance (SPR), we performed in vitro phenotypic analyses to systematically evaluate the inhibitory effect of Iso on OC differentiation. The mechanisms behind Iso’s inhibition of OC differentiation were further elucidated. In vivo testing was also performed to substantiate the therapeutic effects of Iso in an OP animal model.ResultsAt low concentrations, Iso showed no cytotoxicity and did not interfere with cell proliferation in RAW 264.7 cells. Iso effectively inhibited RANKL-induced osteoclast differentiation in these cells, while downregulating related genes levels (Nfatc1, Ctsk, Trap, c-Fos). Molecular dynamics simulations and surface plasmon resonance confirmed Iso’s dual binding to both RANKL and RANK. KEGG pathway enrichment analysis results indicated that Iso modulates the MAPK, NF-κB/PI3K-AKT, and calcium signaling pathways. Western blot analysis revealed that Iso treatment targeting the RANKL/RANK binding pathway significantly downregulated phosphorylation levels of JNK, P38, AKT, and p65. Concurrently, Iso stimulation markedly increased IκBα expression, thereby rescuing its degradation. Furthermore, Iso demonstrated a robust inhibitory effect on reactive oxygen species levels in vitro. Furthermore, in OVX mice, Iso treatment increased bone density, modulated serum bone metabolism markers, and downregulated transcriptional levels of OC marker genes.ConclusionIso exhibits therapeutic potential for OP by selectively targeting and disrupting the RANKL-RANK interaction. This intervention modulates the expression of intracellular transcription factors and multiple signaling pathways, thereby inhibiting the maturation of OCs. Through mitigating OC-mediated bone loss, Iso holds significant promise as a potent therapeutic agent for OP.